STRATEGI PENGEMBANGAN JELEKONG SEBAGAI DAERAH TUJUAN WISATA DI KABUPATEN BANDUNG (LOKASI STUDI: KELURAHAN JELEKONG, KABUPATEN BANDUNG) - Nuansa A, Hamam; Lestari, Forina; Medtry, Medtry (Jurnal Master Pariwisata (JUMPA); Volume 10, Nomor 01, Juli 2023, 2023)
Jelekong is an educational tourism village located in Baleendah District, Bandung Regency. It offers a typical rural panorama, a center for making wayang golek crafts, Sundanese art performances, and a producer of paintings with artistic and cultural value. This research has aims to formulate a tourism development strategy with an existing art and cultural approach. The methods used in the research include identifying the characteristics of tourist objects, including attractions, amenities, accessibility, and management, identifying visitor characteristics, and formulating tourism development strategies from the results of the SWOT analysis. The analysis results show that the great potential for edutourism in this area is still faced with several obstacles, such as lack of promotion, the need for regional arrangement, and collaboration with various parties. Some of the strategies that have been formulated are expected to support the development of tourism in Jelekong Village such as strengthening the promotion of the attractiveness of art education tourism in Jelekong Village, strengthening management through technology training and promotion for Kompepar as the manager, improving the quality of existing facilities in the tourist village. Keywords: tourism development strategy; edutourism; creative village; Jelekong Village.